The Measurement of Democracy Indicators in Islamic Republic of Iran (1979-2013) - heidar shahriari (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2020)
The purpose of this article is to survey the historic process of democracy in Iran after Islamic revolution by benefiting from Robert Dahl’s polyarchy model and qualifying his threefold indexes as political participation, political competition and political supervision and their mixture through Boolean algebra technic as to show the historic fluctuation process of democracy in Iran after revolution. By periodization the history after Islamic revolution into four periods, i.e. first period (1979-82), second period (1982-98), third period (1988-2006), fourth period (2006-2013), the collected data show that the amount of democracy indicators has fluctuated over time except the period of 1979-1982, but, the fluctuation has leaned to up, not down. In spite of affluent sources which have surveyed this topic mostly qualitatively or have surveyed some parts of this topic, this article has attempted to survey the different parts of this topic methodically and quantitatively through mixed method; this article has also received an outcome that the historic process of democracy in Iran after revolution has progressed so far, and presumably it would progress in future if its looked through a historical sociology.